EVALUAREA FORMATIVĂ A COMPETENȚEI DIGITALE LA STUDENȚII FILOLOGI - Tatiana VEVERIŢA (Moldova State University, 2018)
În articol sunt prezentate unele elemente, repere și modalități de implementare a procedurii de evaluare formativă a competenței digitale la studenții filologi. Sunt valorificate metoda proiectului și metoda portofoliului digital (pe exemplul soluțiilor web 2.0.) în evaluarea abilităților de utilizare a tehnologiilor informaționale. FORMATIVE EVALUATION OF DIGITAL COMPETENCE WITH STUDENTS PHILOLOGISTS This article highlightes some benchmarks and ways to implement the formative assessment of digital competence with students philologists. In this paper the benefits of digital portofolio and project method (on the example of web 2.0.) in formative evaluation of skills of using Information Technologies were investigated.